2021
DOI: 10.3390/molecules26216696
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Anthocyanin Profiles of Different Vitis amurensis Grape Cultivars and Hybrids from Chinese Germplasm

Abstract: To evaluate the important Vitis amurensis germplasm, the quality characteristics and anthocyanin profiles of the ripe berries of 20 V. amurensis grapes and 11 interspecific hybrids in two consecutive years were analysed. Compared with the V. vinifera grapes, V. amurensis grapes had small berries with low total soluble solids and high titratable acids, and were richer in phenolic compounds except for flanan-3-ols in their skins but had lower phenolic contents in their seeds and showed lower antioxidant activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The antioxidant activity of grape seed extracts significantly (p < 0.05) correlated with TPC (Table 2), which confirms the well-known fact that phenolic compounds are responsible for the antiradical activity and reducing power of grape seeds and their extracts [18,37,40]. Pearson's correlation with a high correlation coefficient (0.853) was also found between DPPH • scavenging activity and ORAC (Table 2).…”
Section: Antioxidant Activitysupporting
confidence: 77%
See 3 more Smart Citations
“…The antioxidant activity of grape seed extracts significantly (p < 0.05) correlated with TPC (Table 2), which confirms the well-known fact that phenolic compounds are responsible for the antiradical activity and reducing power of grape seeds and their extracts [18,37,40]. Pearson's correlation with a high correlation coefficient (0.853) was also found between DPPH • scavenging activity and ORAC (Table 2).…”
Section: Antioxidant Activitysupporting
confidence: 77%
“…This could have resulted from methodological differences (e.g., results were expressed in (+)-catechin equivalents and a higher extraction temperature was applied) and from the use of a different batch of materials and reagents. A higher TPC of seeds of V. vinifera compared to V. amuresnsis was noted by Zhu and co-workers [ 37 ]. In turn, Liang and co-workers calculated the content of total phenolics as a sum of 28 individual compounds determined by HPLC-MS and found that, similar to our study, the value for V. amurensis seeds was lower than for V. riparia seeds, but V. vinifera seeds had a significantly higher content of phenolics among the three Vitis species (approximately 5 and 3 times higher, respectively) [ 34 ].…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Wild Vitis species (such as Chinese and North American grapes) have high levels of diglucoside anthocyanins or even triglucosides (Mazzuca et al., 2005; Narduzzi et al., 2015; Teissedre, 2018; Zhu et al., 2021). These are generally only present in trace amounts in V. vinifera .…”
Section: Chemical Composition Of Hybrid Grape and Wines And Its Impac...mentioning
confidence: 99%